Economic model system of chronic diseases in Australia: a novel approach initially focusing on diabetes and cardiovascular disease. (13th October 2010) - Walker, Agnes; Butler, James R.G.; Colagiuri, Stephen
Chronic diseases affect around 80% of older Australians, are main causes of premature death, and account for 70% of health expenditures. The novel features, building and validation of an Australian prototype model-system which simulates interventions that target several chronic diseases are described. Chronic disease progression models are linked to a population-wide microsimulation projection model that accounts for demographic, socio-economic and health characteristics, comorbidities, health expenditures, quality of life. It estimates costs vs. benefits of simulated policy interventions. The outcome is a validated person-level prototype able to simultaneously model diabetes and Cardiovascular Disease (CVD). An illustrative model application is also presented.